Plasma Membrane Calcium Pump (PMCA) Differential Exposure of Hydrophobic Domains after Calmodulin and Phosphatidic Acid Activation - Mangialavori, Irene (American Society for Biochemistry and Molecular Biology, 2011)
The exposure of the plasma membrane calcium pump (PMCA) to the surrounding phospholipids was assessed by measuring the incorporation of the photoactivatable phosphatidylcholine analog [(125)I]TID-PC/16 to the protein. In the presence of Ca(2+) both calmodulin (CaM) and phosphatidic acid (PA) greatly decreased the incorporation of [(125)I]TID-PC/16 to PMCA. Proteolysis of PMCA with V8 protease results in three main fragments: N, which includes transmembrane segments M1 and M2; M, which includes M3 and M4; and C, which includes M5 to M10. CaM decreased the level of incorporation of [(125)I]TID-PC/16 to fragments M and C, whereas phosphatidic acid decreased the incorporation of [(125)I]TID-PC/16 to fragments N and M. This suggests that the conformational changes induced by binding of CaM or PA extend to the adjacent transmembrane domains. Interestingly, this result also denotes differences between the active conformations produced by CaM and PA. To verify this point, we measured resonance energy transfer between PMCA labeled with eosin isothiocyanate at the ATP-binding site and the phospholipid RhoPE included in PMCA micelles. CaM decreased the efficiency of the energy transfer between these two probes, whereas PA did not. This result indicates that activation by CaM increases the distance between the ATP-binding site and the membrane, but PA does not affect this distance. Our results disclose main differences between PMCA conformations induced by CaM or PA and show that those differences involve transmembrane regions.